Analisis Butir Soal Tes Kemampuan Siswa pada Mata Pelajaran Manajemen Perkantoran - Miftahir Rizqa; Melly Andrina; Putri Puja Lestari; Kurniawati Fitri Indriyani; Ulmi Hidayanti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Many students have difficulty in answering the questions given, which indicates that the quality of the questions given is not optimal, this has an impact on the accuracy of assessing student abilities and the effectiveness of learning. This study aims to evaluate the quality of test items that have been used and examine several important aspects in item analysis such as Validity, Reliability, differentiating power and difficulty level of questions. This research uses a quantitative approach with descriptive methods to evaluate the results of research on student ability test questions in office management subjects. Data collection techniques are done through documentation and test techniques. Documentation is done by collecting student answer sheets that have done multiple choice tests. The test was conducted online using the Google Form platform, consisting of forty-five multiple choice questions. While the data analysis technique in this study used the help of Microsoft Excel 2013 and analyzed the validity and reliability of the items using SPSS version 16.0 with a focus on the Validity, Reliability, differentiating power and difficulty level tests. As for the results of the study, it was found that the validity of the items was in a fairly high category, the reliability index was high, the level of difficulty was in the category of 11 easy questions, 34 medium questions, and for the differentiating power included in the excellent category.